GREEN FINANCE FOR SUSTAINABLE AGRICULTURE AND FOOD SYSTEMS - Khujanazarova, Nargis; Abdullayeva, Sharbat (SAMBHRAM XABARNOMASI, 2024)
Annotation This article presents the trends in the development of green finance for sustainable agriculture and food systems for achieving the United Nations Sustainable Development Goals by 2030. Because a sustainable future is not possible without eradicating poverty and hunger. Ensuring food security for every one of the key functions and a difficult task for agriculture, which is faced with growing difficulties. Population growth, the accelerating pace of urbanization, and rising income levels are increasing the burden on the agricultural sector associated with the need to meet the demand for safe and nutritious food. Agriculture must ensure decent work and support sources livelihoods of billions of rural residents’ areas around the world, especially in developing countries. Where levels of hunger and poverty are highest. However, one of its strengths as a concept is the implication that there is a need to reconcile economic development, the quality of life, and the environment, within various political frameworks that interrelate at the international and global levels. Keywords: Green finance, financial resources, agriculture and food systems, sustainable development goals.